A six-term novel chaotic system with hidden attractor and its circuit design - Mamat, Prof. Dr. Mustafa (Springer International Publishing, 2018)
In this work, we propose a six-term novel 3D chaotic system with hidden attractor. The novel 3D chaotic system consists of sic terms and two quadratic nonlinearities. We show that the novel chaotic system has no equilibrium point and hence it exhibits hidden attractor. A detailed qualitative analysis of the 3D chaotic system is presented such as phase portrait analysis, Lyapunov exponents, bifurcation diagram and Poincare map. The mathematical model of the novel chaotic system is accompanied by an electrical circuit implementation, demostrating chaotic behavior of the strange attractor. Finally, the circuit experimental results of the chaotic attractors show agreement with numerical simulations.